Romantic relationships and use of social networks and instant messaging among students from the University of the Balearic Islands - Casero Martines, Antonio (2016)
In order to describe the pattern of use of interactive devices and their connection with the status of romantic relationships, a questionnaire was prepared and applied to 776 students from the University of the Balearic Islands (UIB, Spain), using a mixed and multistage sampling method. By means of tests of independence, mean comparison tests, as well as ANOVA, parameters of use on social networks and instant messaging were analyzed, including habit, application, and feelings of deprivation, etc., regarding the status and duration of romantic relationships. Main findings show Facebook and WhatsApp as the most dominant apps, even in the classroom, where boredom and the need to disconnect from the class are the most widely used arguments to justify the non didactic use of the apps during class. Significant differences in the duration of the couple and the general use of these apps were also detected, as well as self-reported feelings of discomfort by deprivation.